Association between psychological symptoms and illegal driving behaviors in a sample of Chinese private car drivers - Chen, Hongguang; Li, Hui; Pu, Changqin; Xu, Hubo; Wang, Tingwei; Du, Ling; Liu, Xiuxiu; Li, Shunfei; Li, Mengqian (Frontiers in Psychiatry, 2022)
Background: Findings on the associations between psychological symptoms and driving behaviors in private car drivers are inadequate. Method: The study consisted of 3115 private car drivers in Yulin, China. The measurements included information on sociodemographic data, traffic violations, accidents, and Symptom Checklist-90 (SCL-90). In addition, an ordered logistic regression model was employed to examine the association between each psychological symptom and risky driving behaviors. Results: The overall prevalence rate of any self-reported psychological symptom was 10.24%, with 9.22% for males and 11.49% for females. Among them, obsessive-compulsive, interpersonal sensitivity, additional items, hostility, and depression were the five most common psychological symptoms, with prevalence rates of 7.90%, 6.29%, 6.00%, 5.91%, and 5.62%, respectively. Any psychological symptom factor was associated with a higher risk of traffic violations and accidents. However, the intensity of the correlations varied, with obsessive-compulsive symptoms the strongest in general traffic violations and anxiety symptoms in traffic accidents. All psychological symptoms except phobic anxiety and paranoid ideation contributed to a higher risk of failing the driver's license test. Conclusions: The prevalence rate of psychological symptoms was high in private car drivers. This study calls for an urgent need to establish a pilot tertiary prevention strategy to reduce risky driving behaviors through psychological symptoms screening and interventions among private car drivers.